Identifikasi Bakteri Escherichia coli dalam Air Minum Galon pada Kantin yang ada di Universitas Andalas Padang - Gitawama, Muhammad Rayhan Braja; Suharti, Netti; Harminarti, Nora (Faculty of Medicine, Universitas Andalas, 2021)
The National Food and Drug Agency has controlled the refill drinking water in drinking water depots and also controlled food at school canteens ranging from elementary, junior high, to high school, but the National Food and Drug Agency never do food quality controlling in canteens at universities. Objectives: To identified the contamination by coliform and E. coli bacteria in drinking water at Andalas University canteen. Methods: This research was descriptive to identify coliform bacteria on 15 drinking water at the Andalas University faculty canteens. Samples were taken directly using a sterile bottle, while data analysis using Most Probable Number (MPN) tables 5-1-1 and the presence of E. coli bacteria colonies from drinking water samples. Results: 9 of 15 water samples were contaminated by coliform bacteria with the highest MPN index of 240/100 ml that was found in 2 samples. From 9 samples containing coliform bacteria, all of them were found to contain E. coli bacteria. Conclusion: Most of the samples were contaminated by coliform and E. coli bacteria. Drinking water served using a kettle was more contaminated than drinking water served using gallons.Keywords: Coliform, Escherichia coli, MPN